Kesejahteraan Guru Pendidikan Agama Islam dan Implikasinya Terhadap Mutu Pendidikan: Sebuah Analisis Teoretis Multidimensi - Musyrifah Zidni Baroroh; Moh. Sugeng Solehuddin; Abdul Khobir; Slamet Untung; Sopiah Sopiah (LPPM Institut Pendidikan Nusantara Global, 2026)
The low welfare of Islamic Religious Education (PAI) teachers in Indonesia represents a systemic paradox. Recent national reports indicate that a significant proportion of non-civil servant teachers receive salaries below the regional minimum wage, highlighting a structural welfare gap. This study aims to (1) map the welfare problems of PAI teachers in financial, psychological, and professional dimensions during the 2021–2026 period, (2) analyze the implications of welfare deficits on the quality of educational processes and outcomes, and (3) formulate integrative policy solutions based on modern management theory and Maqasid al-Shariah. This study employs a systematic library research design by reviewing 35 scholarly articles indexed in Sinta and Scopus databases published between 2021 and 2026. The inclusion criteria include relevance to teacher welfare, educational quality, and Islamic education, while exclusion criteria include non-peer-reviewed sources and outdated publications. The data are analyzed qualitatively using a descriptive method, applying the frameworks of Motivation–Hygiene Theory (Herzberg), Maqasid al-Shariah Theory (Al-Shatibi), and Total Quality Management (TQM). The findings indicate that welfare deficits are primarily associated with financial insecurity, excessive administrative workload, and limited professional development opportunities. These conditions significantly affect pedagogical performance and reduce the effectiveness of character education.